Source Base Study of Ukrainian-Canadian Educational Ties (Second Half of XX – Beginning of XXI Century) - Sytnyk, Nataliya (Pedagogical Discourse, 2013)
This article analyzes the source base study of Ukrainian-Canadian educational ties over the past decade. Sources of the studied problem are divided into five groups: 1) unpublished documentary material stored in state archives of Ukraine and Canada and in the archives of NGOs in both countries, and; 2) published documentary materials of state bodies in Canada and Ukraine, Ukrainian Canadian community organizations and Ukrainian teachers 3) scientific, methodological and educational literature; 4) publications in Ukrainian and Canadian which have the source character; 5) memoirs and letters of participants of international educational relations of the studied period. Each group of sources is characterized. The first group includes the official documents of the government of Canada and Ukraine – the texts of agreements on cooperation between the Ministry of Education of Ukraine and certain provinces of Canada, reports on the implementation of the agreements of intergovernmental level, cooperation agreements of provincial education departments of our state and provincial ministries of education in Canada, as well as relevant documents of universities of both countries. They contain information / materials and similar statistics that make it possible to determine the main directions, contents, intensity and results of cooperation of both educators and community organizations to identify their influence on the national education system in Ukraine, enriching educational experiences of participating countries. The second group consists of the source base documents of state education bodies of Canada and Ukraine and interested NGOs, published in their officiаl publications (print and electronic) and presented in the pages of educational media. It is primarily journals »Ridna Shkola», »Pochatkova Shkola», »Higher Education in Ukraine», »Vyshcha Shkola Ukrainy», newspapers «Education in Ukraine», «Education» and regional educational journals of our country, as well as periodicals Ukrainian Diaspora – Magazines «Vidhuknitsya», «Ridnoshkilnyk», «Life and School», «Theme», «Journal of CIUS» and others. The third group, which includes scientific, educational and methodical literature, published over the past three decades in both countries is characterized ,as it is the real result of multidimensional cooperation of teachers and scholars participating states. It should be noted that there are no monographic studis on the presented problems. However the collective work of local historians is worth of our attention. The important source of especially authentic materials on the stated problem is the publication in periodicals of Western Ukrainian diaspora and national periodicals during the studied period. The most interesting information is presented by such publications as «Vidhuknitsya» – informational and analytical edition of the World Educational Coordination Council , which in recent years has shifted to the electronic version of delivering information. It should be mentioned that this function it carries on this mission today. On its pages official documents (decrees, decisions, guidelines) of governing bodies of native language schooling in the Ukrainian diaspora that guide the activities of all national organizations of Ukrainians worldwide are published. The publications of the magazines «Life and School», «Ridnoshkilnyk», «Theme» contain material on various forms and methods of cooperation in the field of native language Ukrainian education in different countries of the world, which make it possible to analyze linguodidactic principles of the theory and practice of teaching the Ukrainian language in a multicultural environment. Materials of Ukrainian -Canadian cooperation in education, its formation and development stages systematically presented in national educational publications, including newspapers, «Education», «Education of Ukraine», «Holos Ukrainy», magazines «Ridna Shkola», «Pochatkova Shkola», «Mandrivets» and others. Analysis and interpretation of them allows you to create a true picture of the Ukrainian –Canadian educational ties in the second half of the twentieth – the first decade of the XXI century. The essence of such principles of historical and pedagogical research as historicism, consistency, objectivity, circumstantiality, continuity is shown.